Przekształcenia ludnościowe i gospodarcze na obszarze między aglomeracjami Wrocławia i Opola w latach 1994-2003 - Słodczyk, Janusz; Szafranek, Edyta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The processes of demographic and economic transformations in regional systems depend on disparities of internal functional and spatial structures as well as on external conditionality. The paper is an attempt to identify factors of demographic and economic transformations in Opolskie region. The transformation was caused mainly by interaction of Wroclaw and Katowice agglomerations and A4 highway. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 106-116